Dependently independent: Co-existence of institutional logics in the recorded music industry - Margrét Sigrún Sigurdardottir (Copenhagen Business School (CBS), 2010)
The concept of institutional logics, notably a choice between multiple logics, has been offered as a foundation to theoretically explain heterogeneity of organisation. The thesis focuses on how this heterogeneity of organisation is possible through a study of how decision makers deal with conflicting yet coexisting logics in their every day work. The field chosen for the empirical study is the recorded music industry, where two opposing logics, the artistic and the commercial, necessarily co-exist. Through semi-structured interviews, decision makers in the recorded music industry in the UK were asked about their work processes. Their descriptions revealed two very different ways of acting based on either the artistic logic or the commercial logic. The study further shows that even if there were some attempts to take both logics into account, all the respondents emphasised one logic over the other, but not the same logic, leading to the established major/independent duality in the structure of the field.
hdl:10398/7992
Keywords: 650